1999
DOI: 10.1046/j.1365-2222.1999.00543.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergenic differences between the domestic mites Blomia tropicalis and Dermatophagoides pteronyssinus

Abstract: These results provide evidence that Bt allergens are distinct and have relatively low to moderate cross-reactivity with Dermatophagoides spp. allergens. Bt allergens should therefore be included in the diagnostic panel for the evaluation of allergic disorders in the tropics, and the development of new diagnostic and therapeutic strategies should include allergens of Bt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 33 publications
4
80
0
3
Order By: Relevance
“…The remaining 62 sera were from patients sensitized to either Der p 1 or Der p 2 or both. In data not shown, 22 of the 62 sera (35.5%) had IgE antibody binding to rDer p 5, in agreement with the range of reported prevalences of IgE antibody to this allergen (7,8,32,33), indicating that this construct is a good model of the natural allergen.…”
Section: Resultssupporting
confidence: 83%
“…The remaining 62 sera were from patients sensitized to either Der p 1 or Der p 2 or both. In data not shown, 22 of the 62 sera (35.5%) had IgE antibody binding to rDer p 5, in agreement with the range of reported prevalences of IgE antibody to this allergen (7,8,32,33), indicating that this construct is a good model of the natural allergen.…”
Section: Resultssupporting
confidence: 83%
“…Other than the low to moderate cross-reactivity between group 5 and group 21 allergens, the cross-reactivity of the same group 21 allergens from B. tropicalis and Dermatophagoides mites that have moderate sequence identities is also low to moderate, e.g., sequence identities between Blo t 21 and Der f 21. This low to moderate cross-reactivity among the same group of allergens with moderate sequence identities from B. tropicalis and Dermatophagoides mites is also observed between Blo t 5 and Der p 5 (12), between Blo t 1 and Der p 1 (14), and between Blo t 10 and Der p 10 (11). The results presented in this study are in agreement with the notion that B. tropicalis is a major source of dust mite allergens in the tropics and subtropics that is distinct from Dermatophagoides mites (4).…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, they only cross-inhibit at a low or moderate level, as determined by extensive in vitro and in vivo studies (11)(12)(13)31). Here, we confirm that Blo t 5 can inhibit moderately, with an average of 66.7% (range, 42.6 -87.2%) of IgE binding to Der p 5; by contrast, Der p 5 can only inhibit very weakly, with an average of 10.6% (range, 1.5-29%) of IgE binding to Blo t 5 (Fig.…”
Section: Low To Moderate Cross-reactivity Between Blo T 21 Blo T 5 mentioning
confidence: 99%
See 1 more Smart Citation
“…B. tropicalis extract was able, to a low to moderate degree, to inhibit HDM-speci®c IgE-binding and vice versa in atopic patients in Colombia and Singapore (66, 84). CIE/ CRIE results suggested that HDM and B. tropicalis had two to four similar allergens (84,85). Dot-plot inhibition studies indicated that the cross-reactive allergens are not closely related to Der p 1, Der p 2, and Der p 5, and only a moderate cross-reactivity was shown between the recombinant Der p 5 (rDer p 5) and rBlo t 5 (84).…”
Section: Storage Mitesmentioning
confidence: 99%